2005
DOI: 10.4049/jimmunol.175.12.8392
|View full text |Cite
|
Sign up to set email alerts
|

Global Natural Regulatory T Cell Depletion in Active Systemic Lupus Erythematosus

Abstract: The immune defect that could account for the multisystemic involvement that characterizes systemic lupus erythematosus (SLE) remains unknown. We hypothesized that iterative disease flares correspond to a recurrent defect in the peripheral immune suppression exerted by naturally occurring T regulatory cells (Tregs). Surprisingly, Tregs isolated from lupus patients show the same phenotypic and functional characteristics as corresponding cells found in healthy controls. A decrease in the proportion of circulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
321
9
8

Year Published

2007
2007
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 418 publications
(360 citation statements)
references
References 61 publications
(85 reference statements)
22
321
9
8
Order By: Relevance
“…Our finding of a normal frequency and normal apoptosis sensitivity of Treg differs from previously published data in patients with SLE and, therefore, distinguishes patients with CLE from patients with an active flare of a systemic manifestation of the disease (14-17,32). However, more work needs to be performed with regard to the suppressive activity of Treg, because our study in CLE patients and the study by Miyara et al (16) in SLE patients did not demonstrate a significant reduction in suppressive activity of Treg, while other groups of investigators demonstrated reduced suppressive activity of Treg in patients with SLE, as reported at several meetings (31,32,35).…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…Our finding of a normal frequency and normal apoptosis sensitivity of Treg differs from previously published data in patients with SLE and, therefore, distinguishes patients with CLE from patients with an active flare of a systemic manifestation of the disease (14-17,32). However, more work needs to be performed with regard to the suppressive activity of Treg, because our study in CLE patients and the study by Miyara et al (16) in SLE patients did not demonstrate a significant reduction in suppressive activity of Treg, while other groups of investigators demonstrated reduced suppressive activity of Treg in patients with SLE, as reported at several meetings (31,32,35).…”
Section: Discussionmentioning
confidence: 51%
“…Recently, we reported that the majority of CD4ϩ,CD25 high Treg are highly sensitive to CD95L-mediated apoptosis, in contrast to Tcon (29). Moreover, Miyara et al (16) suggested a loss of Treg due to enhanced sensitivity of Treg to CD95L-mediated apoptosis in SLE. Therefore, we purified CD4ϩ,CD25 high Treg and CD4ϩ,CD25Ϫ Tcon from patients with various subtypes of CLE and tested the sensitivity of these cells to CD95L, in a kill assay as described previously (29).…”
Section: Cd4؉foxp3؉ T Cells In the Skin Of Patients With Clementioning
confidence: 91%
See 3 more Smart Citations